A comparison of pathological methods of measuring lung cancer volume. Issue 8 (August 1996) - Binks, S; Clelland, C A; Layton, C
Abstract : AIM: To determine which of several pathological methods of measuring lung cancer volume compared most favourably with the gold standard. METHODS: Three pathological methods were used on 54 resected lung cancers: (1) measuring the maximum dimension and assuming a spherical shape; (2) measuring three dimensions and assuming an ellipsoidal shape; and (3) deriving the volume from the area of tumour on sequential 1 cm slices using a photocopier and an image analysis system. The gold standard was obtained from the area of whole mount tumour sections on sequential 0.1 cm slices of eight cancers. RESULTS: Volumes derived from 1 cm lung slices gave results closest to our gold standard but assuming tumours were ellipsoidal was only a slightly less accurate and less time consuming method. Assuming cancers were spherical resulted in gross overestimation of the tumour volumes. CONCLUSIONS: For practical purposes, it is reasonable to measure three dimensions of a lung tumour at sectioning and calculate the volume using the formula for an ellipsoid (V = 4/3 pi d.e.f, where d, e and f are the semi-axes).